YURII STEFANYK’S LETTERS: “EVERYONE HAS TO ASCEND HIS CALVARY ON THEIR OWN” - Baran, Ye. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the correspondence of Vasyl Stefanyk’s son Yurii, where the personality (human and creative) of Vasyl Stefanyk is disclosed.